The Politics of Education in Kenyan Universities: A Call for a Paradigm Shift - Chege, Mwangi; Embeywa, Henry (Cambridge University Press, 2009)
The winds of political change have been sweeping across Kenya for the last two decades. However, as many sections of society?the media, the church, civil society, and even ordinary people?take advantage of the unprecedented democratic space in which to engage the political establishment, the country's intelligentsia has remained aloof. The aim of this article is to interrogate discourse patterns in the Kenyan university system. Adopting a historical lens, it argues that the curtailment of intellectual freedom in the postcolonial Kenyan university is a reproduction of the colonial suppression of discourses whose objective was to ensure the political survival of the ruling class. It